Transformasi Pemasyarakatan melalui Community Based Correction: Strategi Rehabilitasi dan Reintegrasi Berbasis Komunitas - Mitro Subroto; La Ode Muhammad Aldhian Putra Hadini (Bestari: Jurnal Pengabdian Kepada Masyarakat, 2024)
AbstrakThe correctional system in Indonesia faces challenges in achieving the goals of rehabilitation and reintegration of inmates into society. Community Based Correction (CBC) emerges as an innovative strategy emphasizing the role of the community in the rehabilitation process. This study examines the transformation of the correctional system through the application of CBC, focusing on community-based rehabilitation and reintegration strategies. Using a qualitative approach, this research analyzes the effectiveness of CBC in enhancing community involvement, reducing stigma against former inmates, and fostering pro-social behavior. The findings indicate that CBC strengthens social ties between inmates and the community, increases participation in rehabilitation programs, and reduces recidivism rates. However, the success of CBC relies on policy support, officer training, and active local community engagement. This study recommends strengthening collaboration between correctional institutions, local governments, and communities to optimize CBC implementation. Through this approach, the correctional system can transform into a more humane and effective model for achieving social reintegration.Keywords: Community Based Correction, Social Reintegration, Rehabilitation